Positive Persistent Visual Symptoms (Visual Snow) Presenting as a Migraine Variant in a 12-Year-Old Girl - Simpson, Jane C.; Goadsby, Peter J.; Prabhakar, Prab (Pediatric neurology, 2013)
Migraine is a common neurological disorder affecting children, in which the headache is often preceded or accompanied by a complex of neurological symptoms known as an aura. Persistent visual symptoms are rare, with typical visual aura sometimes being poorly distinguished from other visual disturbances. We describe the case of a 12-year-old girl who has experienced persistent, constant symptoms throughout the visual fields of white, bright, jagged spots and black and white flashes with sparkles and dots since May 2010. She also has palinopsia, squiggles, and photophobia. The child's drawing of her visual symptoms helps illustrate the case and illuminate her ordeal. The child's visual symptoms have so far been resistant to pharmacological therapy. Further insight is needed into this debilitating condition to allow effective management in the pediatric population.